Mechanical properties and microscopic mechanisms of carbon curing-alkali activation modified iron tailings - Pengfei Wei; Wei Wang; Yanfei Yu; Xingchen Hu; Biao Wang; Na Li; Ping Jiang (Materials Research Express)
Seeking ways to effectively utilise iron tailings within the green building sector is a pressing issue at present. In this study, using iron tailings as the main raw material and cement as the auxiliary cementitious material, the effects of sodium silicate (SS) content and carbonation curing on the compressive strength, stiffness, microstructure and mineral composition of cemented iron tailings (SSCIT) were investigated. The results showed that a certain amount of SS could increase the strength and stiffness of SSCIT. By adding 6% SS, the strength and stiffness of SSCIT reached the maximum value. The addition of SS promoted the dissolution of silicate minerals, and the generated geopolymerised gel binder filled the pores of specimens, enhanced the bonding force between the interfaces of soil particles, and improved the specimen compactness. However, carbonation curing adversely affected the strength of SSCIT. Carbonation caused the hydration products of SSCIT to change, and the decalcification and decomposition of the C-S-H gel increased the porosity of SSCIT, leading to a decrease in strength. In addition, using iron tailings for road base materials is an efficient and feasible method of utilisation.